The Influence of SSO on the Optimization Result of Nasopharynx Carcinoma Plan - Hua, Xiaolong; Yu, Jianhe; Wang, Lu; Chen, Li; Mu, Yanshu; Xu, Wenjing; Ren, Qun; SONG, Chuanjun; Xu, Hongxia; Dai, Jiaqi (Archives of Clinical and Biomedical Research, 2023)
Purpose: To study the influence of Monaco 5.4 treatment planning system (TPS) on the dosimetry of radiotherapy for nasopharynx carcinoma (NPC) under the condition of different segment shape optimization (SSO) times. Methods: Fifteen patients with T3-4N0-2M0 stage NPC were enrolled, and each case was designed with SSO of 3, 5, 7 and 10 times, respectively. The dose results of the target area and major organs at risk (OARs) were statistically analyzed by DVH statistics. Moreover, the isodose lines of 70, 60 and 54 Gy were intercepted at the same plane in the transverse, coronal and sagittal views, then Monaco scripting was used for statistical analysis. MLCs Average mental complexity summary (MCS) values of each group were calculated and the different rate of dose coverage in the target area was compared. In addition, optimization time, delivery time, segments# and monitor unit (MU#) were obtained and analyzed using the optimization console. The plans were verified and analyzed using ArcCheck phantom. Results: For target area D2, the results of the SSO7 group and the SSO10 group were similar and better than those of the SSO3 and SSO5 groups. Besides, the D2 results of the SSO3 group were markedly higher than those of the other three groups. Results of the maximum dose of the spinal cord, brain stem, and lens and the mean dose and V30 of parotid glands showed the same trend in major OARs. SSO7 and SSO10 shared similar dose results, which were significantly better than similar dose results shared by SSO3 and SSO5. In the dose deprogram distribution of 70, 60 and 54 Gy, partial 70 Gy dose spillover occurred in both SSO3 and SSO5 groups and it was more evident in the SSO3 group. However, no significant dose spillover was found in SSO7 and SSO10 groups. In the sub-field alignment comparison under the same angle, the alignment became more complicated and the sub-fields were smaller as the number of SSO times increased. The MCS value decreased with the increase in the SSO value; the results of the three groups except SSO3 were similar. The results of segment#, MU# and plan delivery time between different SSO groups were slightly different, while the plan optimization time changed significantly. The difference between the SSO3 group and the SSO10 group was more than 500 s. The results were compared in ArcCheck, and no significant difference was observed between the groups. Conclusions: The user-defined SSO function of Monaco 5.4 TPS effectively balances the relationship between plan design efficiency and plan quality. An SSO of 7 is a better value for efficiency and quality in clinical radiotherapy for NPC.